Atuação dos nutricionistas no núcleo ampliado de saúde da família e atenção básica - Bessa, Géssica Pires (2019)
The Unified Health System strengthened the primary health care with the creation of the Expanded Nucleus of Family Health and Basic Care (NASF-AB), which expanded the diversity of professionals and made possible the insertion of the nutritionist. This work aimed to analyze the performance of the nutritionist of the NASF-AB of the municipalities of the health region Centro-Sul, Goiás. It consists of a quantitative and qualitative study developed from telephone interviews through Skype® and MP3 software Skype Recorder for audio recording, using a form with open and closed questions, made with the verbal consent of the interviewees. Thematic content analysis was carried out according to Minayo (2014). The quantitative data were analyzed by Excel® software. The professional profile of nutritionists is marked by a majority of female subjects (93.33%), with a mean age of 31 years, with a low remuneration in relation to the working day, presenting employment relationship, mainly in the form of a contract for the provision of services (66.67%), occupying the position of NASF-AB for less than 11 months (73.33%), who have the basic health units as their main workplace (60.00%), with a higher presence in the Health Program at School (93.33%), in the National Program for Tobacco Control (73.33%), in the Food and Nutrition Surveillance System (60.00%), in the National School Feeding Program (53.33%) and the Bolsa Família Program (53.33%). Through the qualitative analysis, it was possible to verify that important factors for the articulation of nutritionists with the Family Health teams (eSF) are: eSF support, communication, and planning and programming, whose work focuses on the development of support to the SFI in the technical-assistance dimension and the extended clinic. The articulation presents problems related to: precarious working conditions, difficulties with management, lack of adherence and lack of knowledge of the population about NASF-AB. The promotion of adequate and healthy food is developed as food and nutritional education, in lectures and groups, mainly in the BHUs and in the schools with weekly frequency, presenting greater participation of psychologists and of nurses and the public children and youth. The studied region lacks systematic strategies for the qualification of the workforce carried out by nutritionists, who presented misunderstanding about the Permanent Education in Food and Nutrition, as well as complaints about the lack of institutional qualification of this theme. This research was developed in the Professional Master in Collective Health of the Federal University of Goiás and can subsidize the planning of the nutritionist's work in NASF-AB.